Implementasi Problem Based Learning berbasis Numbered Heads Together dan Thinks Pair Share dalam Pembelajaran Matematika ditinjau dari Komunikasi Matematika pada Siswa Kelas XI SMK Negeri 1 Banyudono - Suryani, Dwi; , Dra. Nining Setyaningsih, M.Si (2017)
The aim of this research are to analysis: (1) the ectmodelof learning in mathematics learning outcomes, (2) the effect of mathematics communication in mathematics earningoutcomes, (3) the interaction between the learning model with hematics communication on the results of learning mathematics. This research is a experimentalresearch to treat learning model. The research sample was determined by random cluster ampling technique, in order to obtain class XI AP 2 as the erimental class 1 and class XI AP 1 as an experimental class 2 and class XI PM 1 as the control class. The research instrument used a questionnaire communication of mathematics and matics achievement test. Data analysis techniques to the analysis of variance of two different cell lines. Before the test analysis is done, the sample must do a balance test and the prerequisite test is test of normality and homogeneity test. Based on the research results with significance of 5% was obtained: (1) there is an influence model of the learning outcomes of mathematics, (2) there is no influence of matics communication on the results of learning mathematics, (3) there is no interaction between the learning model and communication of mathematics on learning outcomes in mathematics.